IMPLEMENTASI METODE SAD DHARMA DALAM PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SD NO. 3 LEGIAN - Ni Luh Putu Pradnyadewi; I Ketut Sudarsana; I Dewa Gede Rat Dwiyana Putra (JAPAM (Jurnal Pendidikan Agama), 2025)
Sad dharma is six methods of learning Hindu religious education and character in the concept of Hinduism, including: dharma wacana, dharma tula, dharma yatra, dharma santhi, dharma gita and dharma sadhana. This method aims to actualize religious teachings so that harmony is created in religious life. In learning Hinduism in the formal realm, there is one Hindu religious learning that is important as a form of implementation of religious teachings, these teachings are packaged in the sad dharma method in achieving physical and spiritual happiness, so Hindu religious values ​​are needed as a strengthening fortress. The problems discussed are (1) How is the implementation of the sad dharma method in Hindu religious and character education at SD No. 3 Legian?, (2) What are the obstacles and efforts made in the implementation of the sad dharma method in Hindu religious and character education at SD No. 3 Legian?, (3) What are the implications of the implementation of the sad dharma method in Hindu religious and character education at SD No. 3 Legian?. Based on the research, it can be found: (1) implementation of the sad dharma method in Hindu religious and character education at SD No. 3 Legian, (2) Obstacles and efforts in implementing the sad dharma method in Hindu religious and character education at SD No. 3 Legian, (3) implications of implementing the sad dharma method in Hindu religious and character education at SD No. 3 Legian.